Monitoring Intangible Investment: Case of Tunisian Companies - Mhedhbi, Imen (Journal of Asian Business Strategy, 2013)
Nowadays, the efficiency of the productive and physical investment depends on the intangible investment that is associated him. This last takes a very important place in activities and form a distinctive advantage for the competitiveness of enterprises. But it is again very complex and difficult to be able to follow it respectable. The objective of our work is therefore to look for the method according to which we are going to try to follow them in enterprises. The follow-up of operations of the enterprise is not content any more the analysis of costs it is rather oriented toward the analysis of the value and the performance. It will be made by logic of piloting with the help of a certain number of specific indicators that must be in scorecard of the enterprise. The result of our research in the Tunisian context shows that, in spite, our enterprises are conscious of the importance of the immaterial in their activities and well they invest more and more in the intangible, they remain even incapable to follow efforts and the intangible assets appropriately.